Styling Masculinity : Gender, Class, and Inequality in the Men's Grooming Industry - Barber, Kristen (Book collections on Project MUSE., 2016)
"The twenty-first century has seen the emergence of a new style of man: the metrosexual. Overwhelmingly straight, white, and wealthy, these impeccably coiffed urban professionals spend big money on everything from facials to pedicures, all part of a multibillion-dollar male grooming industry. Yet as the innovative study reveals, even as the industry encourages men to invest more in their appearances, it still relies on women to do much of the work. Styling Masculinity investigates the economic and social relations at the heart of the growing multi-billion-dollar male grooming industry. Conducting detailed observations at two upscale men's salons, Kristen Barber explores both how male customers are encouraged to invest in their appearance and how female employees do much of the work--not only the physical labor of snipping, tweezing, waxing, and exfoliating, but also the emotional labor of pampering their clients and pumping up their masculine egos. Letting salon employees tell their own stories, Barber not only documents occasions when these workers are objectified and demeaned, but also explores how their jobs allow for creativity and confer a degree of professional dignity. In the process, she traces the vast network of economic and social relations that undergird the burgeoning male beauty industry."--Publisher's description.